21 Effects of supplementing late gestation sow diets with zinc on pre-weaning mortality of pigs under commercial rearing conditions. (30th November 2020) - Holen, Julia P; Urriola, Pedro E; Schwartz, Mark; Jang, Jae-Cheol; Shurson, Gerald C; Johnston, Lee
Abstract: The objective of this experiment was to determine pre-weaning survival of pigs when sows were supplemented with 3 dietary levels of Zn in late gestation. Gilts and sows (n = 339) were assigned to one of three dietary treatments based on parity. Treatments were: 1) Control – corn-soybean meal-based diet containing 125 ppm supplemental Zn as ZnSO4 (75 ppm Zn) and AvailaZn™ (50 ppm Zn, CON); 2) Intermediate – as Control + 240 ppm supplemental Zn as ZnSO4 (INT); and 3) High – as Control + 470 ppm supplemental Zn as ZnSO4 (HI). Final supplemental Zn concentrations of diets were: 1) CON – 125 ppm; 2) INT – 365 ppm; and 3) HI – 595 ppm. Sows received dietary treatments from about d 85 of gestation until farrowing. Individual piglet birth weights were recorded within 12 h of parturition and all instances of piglet mortality were recorded. The statistical model considered fixed effects of diet and random effects of parity. Chi-square analysis was used to determine diet effects on piglet mortality. There were no differences in total pigs born, born alive, or weaned per litter. However, piglets from sows fed the INT diet had heavier (P < 0.05) birth weights (1.42 kg) than those fed CON (1.38 kg). Furthermore, incidence of low birth weight pigs was less (P < 0.05) for sows consuming INT compared with sows fed CON and HI (Table 1). Overall piglet mortality tended to decrease (P < 0.10) as dietary Zn increased. Furthermore, mortality of low birth weight pigs decreased (P < 0.05) as dietary Zn increased. Overall, effects of supplemental dietary Zn at 365 and 595 ppm in late gestation improved pre-weaning survival of low birth weight piglets and reduced overall pre-weaning mortality of piglets.